Samiri Tevratı'nın Kökenine Dair Araştırmalar Üzerine Bir Değerlendirme/An Assessment of Research on the Origins of the Samaritan Pentateuch - Fatma Gerçekçioğlu (Oksident)
A historical assessment of the Samaritan Pentateuch is important both for understanding the processes of change and transformation that sacred texts has been through and for exploring how communities with different religious interpretations, though originating from the same region, shape their identities. Various theories exist regarding the origins of this Torah, which is considered sacred by the Samaritan community. Research on the Abisha Scroll, regarded by the Samaritans as one of the oldest and most revered manuscripts, provides insights into the methods this community has employed to preserve and transmit its sacred texts across generations. In this study, claims concerning the origin of the Samaritan Pentateuch are evaluated historically within the context of scholarly research conducted after the discovery of the Abisha Scroll and the Dead Sea Scrolls. Accordingly, the writing process, historical development, and preservation methods of this text will be examined in comparison with Jewish sacred text traditions such as the Masoretic Text, the Septuagint, and the Dead Sea Scrolls. The Dead Sea Scrolls make a significant contribution to research on the origins of the Samaritan Pentateuch. In our study, while examining the similarities of the Samaritan Pentateuch with the Septuagint and the Dead Sea Scrolls, we will reevaluate claims that it is derived from the Masoretic Text.